Respon Siswa terhadap Soal Matematika Mirip PISA dengan Konteks Berintegrasi Nilai Islam - Moch. Lutfianto; Anisa Fatwa Sari (Jurnal Elemen, 2017)
PISA problems are based on real life context. It can be also enriched with Islamic value integration. The aim of this reseacrh is understanding the effect of posing PISA-like problems to students. The research was carried out qualitatively. The problems which are designed with context of Islamic value integration was posed to students. Then, the students filled in a questionare and have been interviewed about their responses on the problems. The results show that all subject being more motivated in doing a good deed suit on Islamic values. They told that they gained new understanding upon Islamic values from the context presented in the problems. They became aware that they will get reward when they practice an Islamic teaching. Some of them think that the problems are quite difficult and even unfamiliar for them. In the other hand, they feel happy because they finally know that the practice of Islamic teaching their doing so far will be rewarded.